The Neubad Plakat : A Contemporary Design Phenomenon - Brechbühl, Erich; Hickmann, Fons; Hinrichs, Lea; Steiner, Sam; Lindhorst-Emme, Sven; Mauchle, Isabelle; Emmenegger, Urs (Karlsruhe : Slanted, 2023)
Aarise ; Dawkins, Aaron ; Karpiel, Adam ; Romano, Alan ; Meyer, Alessia ; Waltenspühl, Amadeus ; Bakken, Anders ; Kiener, Andreas ; Kronenberg, Angela ; Wicki, Anja ; Brunner, Ann-Kathrin ; Kahri, Annie et al.
In the Swiss province, at the foot of picturesque mountains, on a quiet lake, a biotope of avant-garde design has formed. The self-proclaimed “Poster Town” Lucerne has managed to merge the boundaries between art and design, creating a contemporary design phenomenon in the process. We are talking about the posters for the Neubad Cultural Center, which have long since found their way out of the valley and all over the world. The posters, in minimalist black and white, not only set contemporary design trends, but playfully transcend the boundaries of our perceptual habits. Progressive illustration and experimental typography create subcultural codes on a highly cultural level that remain unpretentious despite their artistic daring. The Neubad Plakat is an aesthetic phenomenon and an expression of a social change that has always been expressed in fashion, music, design—in other words, in the zeitgeist. The book as a collection of curated pieces that in itself formulated a new expression of this emerged aesthetic. A Contemporary Design Phenomenon
boek